Chronic Hindlimb Ischemia Impairs Functional Vasodilation and Vascular Reactivity in Mouse Feed Arteries - Cardinal, Trevor R.; Struthers, Kyle R.; Kesler, Thomas J.; Yocum, Matthew D.; Kurjiaka, David T.; Hoying, James B. (Frontiers in Physiology, 2011)
Vasodilation of lower leg arterioles is impaired in animal models of chronic peripheral ischemia. In addition to arterioles, feed arteries are a critical component of the vascular resistance network, accounting for as much as 50% of the pressure drop across the arterial circulation. Despite the critical importance of feed arteries in blood flow control, the impact of ischemia on feed artery vascular reactivity is unknown. At 14 days following unilateral resection of the femoral-saphenous artery-vein pair, functional vasodilation of the profunda femoris artery was severely impaired, 11 ± 9% versus 152 ± 22%. Although endothelial and smooth muscle-dependent vasodilation were both impaired in ischemic arteries compared to control arteries (Ach: 40 ± 14% vs 81 ± 11%, SNP: 43 ± 12% vs and 85 ± 11%), the responses to acetylcholine and sodium nitroprusside were similar, implicating impaired smooth muscle-dependent vasodilation. Conversely, vasoconstriction responses to norepinephrine were not different between ischemic and control arteries, -68 ± 3% versus -66 ± 3%, indicating that smooth muscle cells were functional following the ischemic insult. Finally, maximal dilation responses to acetylcholine, in vitro, were significantly impaired in the ischemic artery compared to control, 71 ± 9% versus 97 ± 2%, despite a similar generation of myogenic tone to the same intravascular pressure (80 mmHg). These data indicate that ischemia impairs feed artery vasodilation by impairing the vascular wall’s responsiveness to vasodilating stimuli. Future studies to examine the mechanistic basis for these observations or treatment strategies to improve feed artery vasodilation following ischemia could provide the foundation for an alternative therapeutic paradigm for peripheral arterial occlusive disease.